Situational judgment test measures administrator computational thinking with factor analysis - Indrawati, Cicilia Dyah Sulistyaningrum; Permansah, Sigit; Ninghardjanti, Patni; Subarno, Anton; Winarno, Winarno; Rusmana, Dede (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Computational thinking skills (CTS) play a crucial role across diverse domains, involving a thinking process that allows the execution of solutions by information processing agents. Measuring the level of CTS becomes essential to ensure that administrators effectively leverage technology. However, finding suitable instruments to measure and justify CTS levels in administration can be challenging. The selection of situational judgement test (SJT) is supported by its validity and reliability in assessing attributes, including professionalism. The instrument’s development includes face validity, discriminant validity (using Pearson correlation and Cronbach’s alpha), and exploratory factor analysis (EFA). The study involved 111 undergraduate administration students from various Indonesian universities, and data were collected in 2023. Following a discriminant validity analysis, ten items were eliminated, while 23 met the criteria with p0.185. Subsequently, EFA yielded 16 items forming seven components, covering algorithmic thinking, problem-solving, technology literacy, problem abstraction, problem reformulation, data management in administration technology, and administrative data presentation with loading factor variations (0.421-0.868). The final instrument, consisting of 16 valid items and seven components, effectively evaluates the level of administrator computational thinking skills (ACTS) among administration students.